2022
DOI: 10.3126/ajms.v13i4.40765
|View full text |Cite
|
Sign up to set email alerts
|

Validation of rapid SARS-COV-2 antigen detection test as a screening tool for detection of Covid-19 infection at district hospital in northern India

Abstract: Background: Testing of samples from suspected SARS-CoV-2 patients with reverse transcription polymerase chain reaction (RT-PCR) may result in delayed detection of infection. Given the number of people affected in pandemic, it is important to use a test that gives faster results and can be used on large number of sample size to cope with the increased testing capacity. Rapid Antigen detection test fulfills both the criteria. Aims and Objectives: The study aims to evaluate the diagnostic accuracy of rapid antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Among the studies done in India, the strength of agreement between these two tests ranged from moderate to almost perfect. A prospective study [21] done among 756 patients from a district hospital in North India shows a substantial agreement like ours with a κ value of 0.6482 (95% CI: 0.5801 to 0.7163). However, Pandey et al found moderate agreement between these two tests [22].…”
Section: Discussionsupporting
confidence: 87%
“…Among the studies done in India, the strength of agreement between these two tests ranged from moderate to almost perfect. A prospective study [21] done among 756 patients from a district hospital in North India shows a substantial agreement like ours with a κ value of 0.6482 (95% CI: 0.5801 to 0.7163). However, Pandey et al found moderate agreement between these two tests [22].…”
Section: Discussionsupporting
confidence: 87%